A few-picosecond and high-peak-power passively mode-locked erbium-doped fibre laser based on zinc oxide polyvinyl alcohol film saturable absorber - Alani, Ibrahim A.M.; Lokman, Muhammad Quisar; Ahmed, Mahmoud Hazzaa M.; Al-Masoodi, Ahmed Hasan Hamood; Latiff, Anas Abdul; Harun, Sulaiman Wadi (IOP Publishing, 2018)
This paper demonstrates a few-picosecond and high-peak-power mode-locked fiber laser, using an erbium-doped fiber as a gain medium and zinc oxide (ZnO) element as a new passively saturable absorber (SA). The ZnO element was synthesized using a seeding solution and amended with a polyvinyl alcohol to form a film. The ZnO has been identified as an ideal SA due to its high nonlinear optical response, high sustainability to damage threshold, and fast recovery time. Self-started mode-locked laser pulses have been generated at a relatively low pump power of 42 mW with a fundamental repetition rate and pulse duration of 3.26 MHz and 2.60 ps, respectively. The proposed laser operates at 1599.5 nm with a 3 dB spectral bandwidth of 1.12 nm. A maximum output power, pulse energy, and peak power of about 6.91 mW, 2.12 nJ, and 0.82 kW, respectively, are obtained at a maximum pump power of 159 mW. From these findings, we confirm that the proposed laser can be viewed as a promising light source in the emerging optical communication system.